Anomalously large resistance at the charge neutrality point in a zero-gap InAs/GaSb bilayer. (31st May 2018) - Yu, W; Clericò, V; Fuentevilla, C Hernández; Shi, X; Jiang, Y; Saha, D; Lou, W K; Chang, K; Huang, D H; Gumbs, G; Smirnov, D; Stanton, C J; et al.
Abstract: We report here our recent electron transport results in spatially separated two-dimensional electron and hole gases with nominally degenerate energy subbands, realized in an InAs(10 nm)/GaSb(5 nm) coupled quantum well. We observe a narrow and intense maximum (∼500 kΩ) in the four-terminal resistivity in the charge neutrality region, separating the electron-like and hole-like regimes, with a strong activated temperature dependence above T = 7 K and perfect stability against quantizing magnetic fields. We discuss several mechanisms for that unexpectedly large resistance in this zero-gap semi-metal system including the formation of an excitonic insulator state.